Studi Etnometodologi Tentang Penerapan Biaya Pernikahan Gorontalo dalam Adat Tolobalango dan Dutu - Nur Ainun Nisya Mohi; Niswatin; Nilawaty Yusuf (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the implementation of Gorontalo wedding costs in Tolobalango and Dutu customs. This research method uses qualitative research methods with an ethnomethodological study approach. Data collection methods were carried out by means of interviews, observation and documentation in the form of notes, photos and recordings. The research location is in Hulonthalangi District, Tenda Village, Gorontalo City. The research results show that there are accounting values ​​contained in Tolobalango and Dutu customs. This is proven by the existence of actions to minimize costs because in this research the two customs were carried out together. This indicates that costs are not just about generating profit or income, but also have important value when viewed from a cultural perspective. And it shows that there are expenses incurred in this wedding ceremony, including: 1) traditional costs, 2) operational costs. Customary fees consist of 1) Tonggu fees; 2) Dingo Fee; 3) Maharru fees; 4) Bungalow Fee. Operational costs consist of 1) Clothing Costs; 2)Makeup Fees; 3)Henna Cost; 4) Catering Costs; 5) Host Fee. The Tolobalango and Dutu traditional processions also contain family values, the value of love and the value of trust.